Investors at Conflict’s Crossroads: an overview of available international courts and tribunals in the Crimean context - Nataliia Tuzheliak (UCL Journal of Law and Jurisprudence, 2017)
The principle of uti possidetis, a Latin expression which stands for a principle in international law that territory and other property remains with its possessor at the end of a conflict has been greatly challenged in recent conflicts and territorial disputes. The annexation of the Crimean Peninsula, the conflicts in Georgia, Cyprus, Syria and Turkey pose questions, such as to what extent states can, may and should guarantee long-term investment protection in the contemporary dynamics of the international legal order. Leaving aside the bigger problem of territorial issues and those related to diplomacy and narrowing the problem down to economic interests and protection of property rights, this paper provides an overview and analysis of the international venues for protection of investors and investment from third states’ conduct outside its borders. This paper analyses the conflict in Crimea, a peninsula located in the south of Ukraine. This case study is used as a backdrop for the examination of investment treaties’ application (and applicability), as well as available protection mechanisms in international law in a context of disputed borders. For full text, please click here
Keywords: Diplomatic Protection; Public International Law; International Law of Human Rights; International Law of Foreign Investment